The Great Mother: A Psychoanalytical Analysis of the Magna Mater In Two Novels - Warda, Wahaj Unnisa (Advances in Social Sciences Research Journal, 2019)
Sigmund Freud formulated the theory of “Oedipus Complex”, Erich Newmann came forth with “The Great Mother or the Magna Mater” based on Carl Jung’s Theory of the Archetype and the Mother Complex, which charts the mental processes of women’s psychological development. Two novels are analysed based on the given psychoanalytical theories the first a British novel “Sons and Lovers” by D.H. Lawrence and the other Australian “The Thorn Birds” by Colleen McCullough. Both novels have two brothers who become the focus of their mother’s attention and the overbearing mother’s control clashes with their identities, which results in death or fallout from society. The characters’ personal conflicts reveal encrypted truth.